Outcomes of DA-EPOCH-R induction plus autologous transplant consolidation for double hit lymphoma. Issue 8 (3rd August 2018) - Chen, Andy I.; Leonard, Jessica T.; Okada, Craig Y.; Gay, Nathan D.; Chansky, Kari; Fan, Guang; Dunlap, Jennifer B.; Raess, Philipp W.; Braziel, Rita M.; Stentz, Alex; Maziarz, Richard T.
Abstract: High-grade B cell lymphoma with MYC and BCL2 rearrangements (double hit) has a poor prognosis with standard R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone). We report here a treatment algorithm of DA-EPOCH-R (dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, rituximab) followed by BEAM (carmustine, etoposide, cytarabine, melphalan) autologous transplant in 36 cases of previously untreated double hit lymphoma (DHL) from 2010 to 2015. A high risk International Prognostic Index (IPI) was present in 42% of cases. At median follow-up of 38 months, the 2-year progression free survival (PFS) and overall survival (OS) were 69% (95% CI 54–84%) and 71% (95% CI 56–86%). Eight cases were refractory to induction with 1-year OS 20%, and no factors were predictive for primary refractory disease. Of 28 responders, 17 proceeded to transplant while 11 were observed, primarily due to age and co-morbidities. By 24-week landmark analysis after diagnosis, the 2-year PFS and OS were both 94% (95% CI 83–100%) vs 79% (95% CI 52–100%) for transplant vs observation ( p = .59 for both PFS and OS). There was no significant benefit to consolidative transplant in our series, and primary refractory DHL needs novel approaches.